PEMANFAATAAN BANTUAN BAZNAS BONEBOLANGO DI KELURAHAN TUMBIHE KECAMATAN KABILA - Moh Fahrezi Arumasi; Harun Blongkod; Sahrain Bumulo (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
This study aims to analyze the impact of Baznas assistance on the welfare of recipients in Tumbihe Village, Kabila District, focusing on how the assistance contributes to improving quality of life and economic empowerment. Baznas assistance not only serves as support for daily economic needs but is also directed toward promoting productive business development, particularly for recipients running micro, small, and medium enterprises (MSMEs). The study employs a qualitative approach using in-depth interviews with purposively selected recipients to obtain relevant and representative information regarding their experiences in utilizing the assistance. The findings indicate that Baznas assistance positively affects family income, saving capacity, and the development of micro-enterprises, including business expansion, increased customer base, and improved product competitiveness. However, the study also identifies several challenges that affect the effectiveness of the assistance, such as difficulty separating business and household finances, limited capital, and unstable business income due to fluctuations in customer demand. These findings underscore that, in addition to fund distribution, continuous mentoring and supervision are necessary to ensure that Baznas assistance is optimally utilized, thereby creating long-term impacts on recipients' welfare.